2013
DOI: 10.1007/s00216-013-7422-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot–NBD–liposome luminescent probes for monitoring phospholipase A2 activity

Abstract: In this paper we describe the fabrication and characterization of new liposome encapsulated quantum dot-fluorescence resonance energy transfer (FRET)-based probes for monitoring the enzymatic activity of phospholipase A2. To fabricate the probes, luminescent CdSe/ZnS quantum dots capped with trioctylphosphine oxide (TOPO) ligands were incorporated into the lipid bilayer of unilamellar liposomes with an average diameter of approximately 100 nm. Incorporating TOPO capped quantum dots in liposomes enabled their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Moreover, the membrane appeared darker than the liposome cavity, which confirms that the QDs were embedded within the lipid bilayers instead of the cavity. This is also in agreement with the study by Kethineedi et al 59 , who observed darker rims of liposomes than the liposome interior upon incorporation of hydrophobic CdSe/ZnS QDs. The fluorescence emission spectra were collected to characterize the fluorescent properties of the QD-embedded POPC/POPE liposomes.…”
Section: Characterization Of Qd-liposomessupporting
confidence: 93%
“…Moreover, the membrane appeared darker than the liposome cavity, which confirms that the QDs were embedded within the lipid bilayers instead of the cavity. This is also in agreement with the study by Kethineedi et al 59 , who observed darker rims of liposomes than the liposome interior upon incorporation of hydrophobic CdSe/ZnS QDs. The fluorescence emission spectra were collected to characterize the fluorescent properties of the QD-embedded POPC/POPE liposomes.…”
Section: Characterization Of Qd-liposomessupporting
confidence: 93%
“…Phospholipase A 2 activity has previously been assayed using titrimetric, colorimetric, fluorometric, and radiometric techniques (Reynolds et al, 1991; Kethineedi et al, 2013). These techniques are time consuming, suffer from limited sensitivity, and present significant safety concerns (Kethineedi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are time consuming, suffer from limited sensitivity, and present significant safety concerns (Kethineedi et al, 2013). For example, early efforts that focused on development of chromogenic PLA 2 assays using sn -2-thioester phospholipids led to PLA 2 -catalyzed formation of sn -2-thiolate to be trapped by reaction with DTNB (5,5’-dithio-bis-2-nitrobenzoic acid).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QD-encapsulated liposome as FRET probe has also been developed for monitoring the enzymatic activity of PLA 2 . 26 …”
Section: Introductionmentioning
confidence: 99%